KEEFEKTIFAN METODE PEMODELAN PADA PEMBELAJARAN BERUPA MENULIS SURAT DINAS SISWA KELAS VII MTS NEGERI 1 PALEMBANG - Charlya, Ika; Hetilaniar, Hetilaniar (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2023)
Based on the results of research and analysis of the average value it can be seen, the test for making official letters for students in the experimental group that applied the modeling method was 83.5, the average score for writing official letters for students in the control group was 70.42 (83.5 > 70,42). The modeling method is more effective when used in delivering official letter writing subject matter. This is shown after testing the mean of the two groups (experimental class and control class) with the price t0 (t count) > t table, namely 1.671 <17.02, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted with evidence of use the modeling method is more effective than conventional methods in learning to write one of the official letters of class VIII MTs students. Country 1 Palembang. Keywords: Modeling method, writing and official letter